KAJIAN KEBIJAKAN PEMERINTAH INDONESIA DALAM PERDAGANGAN CPO INDONESIA MENGGUNAKAN PENDEKATAN ANALISIS INTEGRASI PASAR - Hafizah, Dian (Jurnal AGRISEP, 2011)
Crude Palm Oil (CPO) is one of important commodity for Indonesia. Indonesia is the biggest producers of CPO in the world, and the second exporter after Malaysia.  Despite the fact that Indonesia and Malaysia are mayor CPO exporters, CPO traders determine CPO price in spot market. As a result, Indonesian and Malaysian producers often face price volatilites. Indonesian traders do not have bargaining power in the price determination. On other hands, domestik demands for CPO grow up.  For that reason,  The Indonesian goverment must take a policy to guarantee the fulfilment of CPO needs.  The objective of research are (1) to describe the Indonesian policy in CPO trade that integrated with World market in Rotterdam and Malaysian Market and (2) to formulate the policy implication of CPO price formation in Indonesia. The research showed that Indonesia act as price taker, this is because Indonesian goverment has no bargaining power to determine price in domestic - and international market. To solving the problem is important for goverment to develop CPO’s future market and create product diversification for CPO. Keywords: Crude Palm Oil, Goverment Policy, Price, Integration market